Analisis Bibliometrik Penelitian Artificial Intelligence dalam Islamic Education Menggunakan Vosviewer pada Tahun 2020–2025 - Ahmad, Arbi Salam; Kustati, Martin; Bashori, Bashori (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the development of scientific publications related to Artificial Intelligence in Islamic Education. The analysis was conducted using a bibliometric approach with the assistance of the VOSviewer application. Publication data were collected from the Google Scholar database using the Publish or Perish application. The data consisted of 200 articles published between 2020 and 2025. In 2020, there were 22 articles; in 2021, 35 articles; in 2022, the number increased to 46 articles; in 2023, it further increased to 49 articles; in 2024, there were 36 articles; and in 2025, there were 12 articles. Data analysis was conducted using descriptive quantitative methods and bibliometric mapping through network, overlay, and density visualizations to identify research trends, topic novelty, and thematic density. The results indicate that research on Artificial Intelligence in Islamic Education has shown significant development over the past six years, with a relatively stable increase in publications and a peak in 2023. The most frequently discussed topics are related to technology integration, digital learning, and the development of artificial intelligence-based learning systems in Islamic education. In addition, several topics remain relatively underexplored, providing opportunities for future research in the field of Artificial Intelligence and Islamic Education